1996
DOI: 10.1002/(sici)1096-9861(19960408)367:3<444::aid-cne9>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic expression of calcitonin gene-related peptide (CGRP) immunoreactivity by rat mediobasal hypothalamic neurons

Abstract: Although the hypothalamic arcuate nucleus is a sexually dimorphic region of the rat brain, there are no reports of sex differences in the number of neurons containing specific neuropeptides within this structure. As cells synthesizing calcitonin gene-related peptide (CGRP) have been shown to exhibit sex differences in other steroid-receptive regions of the rat brain, we examined whether the CGRP-immunoreactive cells located in the mediobasal hypothalamus may also be sexually dimorphic. Immunostaining of sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This would indicate that the development of this cell group may not have been completed by E13.5, i.e., the time of VPA administration. Notably, the TH+ cells of the latter region are of mixed catecholaminergic type, e.g., about 60% of the TH+ neurons coexpress calcitonin in A13 (Leclercq and Herbison, 1996), meaning that the effect of VPA may not be confined to the purely dopaminergic phenotype of ventral mesencephalic (VM) neurons.…”
Section: Summary and Interpretation Of Current Findingsmentioning
confidence: 99%
“…This would indicate that the development of this cell group may not have been completed by E13.5, i.e., the time of VPA administration. Notably, the TH+ cells of the latter region are of mixed catecholaminergic type, e.g., about 60% of the TH+ neurons coexpress calcitonin in A13 (Leclercq and Herbison, 1996), meaning that the effect of VPA may not be confined to the purely dopaminergic phenotype of ventral mesencephalic (VM) neurons.…”
Section: Summary and Interpretation Of Current Findingsmentioning
confidence: 99%
“…The CGRP is synthesized throughout the central nervous system. In addition to the spinal cord, brainstem and other parts of the brain, the CGRP is expressed in the different nuclei of the hypothalamus including the arcuate nucleus, lateral hypothalamic and medial basal of the hypothalamus in males and females (Leclercq et al 1996). It has been found that the central injection of CGRP activates the brain areas related to stress while antagonism of CGRP receptors suppresses the anxiogenic behaviors (Sink et al 2011;Rahman et al 2023) Chrysin, a natural polyphenol from the avonoid group, is a bioactive constituent of honey, propolis, and several herbal medicinal herbs such as Passi ora incarnate, Passi ora coerulea, and Oroxylum indicum (Talebi et al 2021).…”
Section: Introductionmentioning
confidence: 99%